2002
DOI: 10.1111/j.1365-2621.2002.tb09444.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endpoint Temperature on the Internal Color of Pork Loin Chops of Different Quality

Abstract: The effects of 5 endpoint temperatures for cooked, internal color were determined for boneless pork longissimus muscle from 4 treatment groups: normal, normal-injected, PSE, and DFD. Visual and instrumental color, myoglobin denaturation, and acid phosphatase (ACP) of raw and cooked samples were evaluated. Visual internal color became (P < 0.05) less pink as endpoint temperature increased; however, DFD chops were more pink (P < 0.05) and PSE chops were less pink (P < 0.05) than other treatments at most endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
4
15
1
2
Order By: Relevance
“…The results were consistent with the values of normal and PSE pork muscles reported by Lien et al (2002) and Nam et al (2001). They showed that RFN pork loin chops had significantly lower color parameters, i.e., Hunterlab L* of 54.6 vs. 61.9 and 48.1 vs. 54.9, and b* of 18.3 vs. 19.9 and 11.0 vs. 12.7, and the lack of difference in a* (10.5-10.7; 7.1-6.6).…”
Section: Colorsupporting
confidence: 94%
See 2 more Smart Citations
“…The results were consistent with the values of normal and PSE pork muscles reported by Lien et al (2002) and Nam et al (2001). They showed that RFN pork loin chops had significantly lower color parameters, i.e., Hunterlab L* of 54.6 vs. 61.9 and 48.1 vs. 54.9, and b* of 18.3 vs. 19.9 and 11.0 vs. 12.7, and the lack of difference in a* (10.5-10.7; 7.1-6.6).…”
Section: Colorsupporting
confidence: 94%
“…These authors found in halothane-carrier pork Longissimus muscles incubated 30 min postmortem at 40°C had significantly lower pH values after 2, 4, 6 and 8 h when compared with normal muscles kept in 4°C. In many previous studies, pork muscles identified to exhibit PSE characteristics typically had an ultimate (24 h) pH significantly lower than that of RFN muscles (pH 5.40-5.60), for example, 5.20 (Lien et al, 2002), 5.32 (van Laack & Kauffman, 1999, and 5.30 (Warner et al, 1997). However, some pork muscles exhibiting PSE-like conditions do show relatively high ultimate pH, for example, 5.47 (Nam et al, 2001), 5.54 (McCaw et al, 1997, and 5.48 (Ryu et al, 2005).…”
Section: Phmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown that higher mean redness values (i.e. a* values) are indicative of a less ''well done'' colouration (Lien et al, 2001a(Lien et al, , 2001b. This is because heating is accompanied by the denaturation of myoglobin and loss of its characteristic bright red colour.…”
Section: Colour Analysismentioning
confidence: 98%
“…A similar pattern was observed for PSE boneless pork chops cooked to the same time/temperature combinations. DFD pork chops have also been tested, and under all cooking conditions, these were more pink than normal or PSE meat (Lien and others 2002a). Myoglobin denaturation is faster in PSE pork when compared to normal pork, particularly at temperatures below 71 °C.…”
Section: The Influence Of Phmentioning
confidence: 99%